Blood levels of circulating methionine components in Alzheimer’s disease and mild cognitive impairment: A systematic review and meta-analysis - Zhao, Yan; Dong, Xinyi; Chen, Bingyu; Zhang, Yizhou; Meng, Sijia; Guo, Fangzhen; Guo, Xiaojing; Zhu, Jialei; Wang, Haoyue; Cui, Huixian; Li, Sha (Frontiers in Aging Neuroscience, 2022)
Background: Circulating methionine components have been reported to be associated with Alzheimer's disease (AD) and mild cognitive impairment (MCI), although outcomes are not always consistent. Methods: Database searching was conducted using PubMed, Embase, Cochrane Library, and Web of Science from inception to December 26, 2021. Two reviewers independently identified eligible articles and extracted the data. We used the Joanna Briggs Institute (JBI) Critical Appraisal tools to assess overall quality of the included studies. STATA software was employed to perform meta-analysis evaluating the standard mean difference (SMD) with its 95% confidence intervals (CI) using random-effects models. Evidence quality was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) criteria. Results: Thirty observational studies were eligible for inclusion. Compared with cognitively normal controls, patients with AD had increased homocysteine (Hcy) levels in the blood (standardized mean differences (SMD)=0.59, 95% confidence interval [CI]: 0.36-0.82, P=0.000), plasma (SMD=0.39, 95% CI: 0.23-0.55, P=0.000), and serum (SMD=1.56, 95% CI: 0.59-2.95, P=0.002). Patients with MCI were not significantly different from controls (SMD=0.26, 95% CI: -0.07-0.58, P=0.127). Patients with AD or MCI did not significantly differ from controls of blood vitamin B12 levels, AD (SMD=-0.05, 95% CI: -0.19-0.08, P=0.440), or MCI (SMD=0.01, 95% CI: -0.16-0.17, P=0.94). Some cohort studies have suggested that higher Hcy, methionine, and S-adenosylmethionine levels may accelerate cognitive decline in patients with MCI or AD, and vitamin B12 deficiency is a risk factor for the disease; however, the results of other studies were inconsistent. Conclusions: Only Hcy levels in the plasma and serum were found to be inversely related to the risk of AD. high-quality longitudinal studies are required to verify these findings (Registration NO. CRD42022308961).